WAJAH BANGSA DALAM CERMIN BUDAYA BERBAHASA - Bustomi Bustomi (IAIN Bengkulu, 2019)
Every nation has different cultural character that initially influences different daily conversation. The culture which means a characteristic and knowledge of a particular group of people encompassing language, religion, and social habit is often used by almost society. It is very much related to the language. Due to natural phenomenon in daily life, something appears in a culture can be reviewed in language. This article is aimed at finding out phenomena of using the Indonesian language which considerably reflects culture of Indonesian societies in thinking and doing something.This study is a qualitative research in nature of which collecting data used is sociolinguistics approach. The data is collected by conducting deep interview and recording spoken and written utterance in natural situation. The result of this study shows that the culture adhering in daily activity of this nation can be detected in daily communication culture. There are many negative cultural utterances reflect negative culture of our nation, namely low self-esteem, irresponsiblity, hidding self-identity, and being a follower of whatever is going on. Seeing the data, it needs cultural improvisation of possitive communication among social interaction. Hence, The role of goverment, educator, mass-media, public official, and public figure are absolutely needed .